Nano Zinc Supplementation: Its Influence on Growth Performance, Feed Intake andHaematobiochemical Parameters in Male Wistar Rats - Akash Mishra; Chander Datt; Kuldeep Dudi; Shambvi; Digvijay Singh (Indian Journal of Animal Nutrition, 2025)
A study was conducted to investigate the effect of supplementation of nano zinc (ZnO-NPs) from zinc oxide source on growth performance, feed intake and hematobiochemical parameters in male Wistar rats. A total of 36 male Wistar rat were taken, where 6 animals were sacrificed at zero days for hematobiochemical studies and rest of the rats were divided into five groups of 6 animals in each. The group T1 was fed purified diet without Zn supplementation. In group T2, 12 ppm inorganic Zn was given while the rats in groups T3, T4 and T5 were supplemented with nano Zn @ 3, 6 and 12 ppm, respectively for five weeks. The average daily gain and feed conversation ratio improved in groups supplemented either with 12 ppm inorganic Zn or with 3, 6 and 12 ppm nano Zn. The plasma ALP activity increased (P < 0.05) with increase in ZnO-NPs while there was a reverse trend for AST and ALT activities. The concentration of total cholestrol and triglycerides decreased (P< 0.5) due to inorganic or ZnO-NPs addition in the diet, however, the effects of 3 ppm ZnO-NPs addition were comparable to those of 12 ppm inorganic Zn or 6 and 12 ppm of nZn. Therefore, supplementation of 3 ppm nano Zn improved growth performance and biochemical parameters in the male Wistar rats and the results were comparable to the groups given either 12 ppm inorganic Zn or 6 and 12 ppm nano Zn.